2021
DOI: 10.1080/07853890.2021.2009554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and associating risk factors of gastrointestinal perforation in children with IgA vasculitis

Abstract: Background IgA vasculitis (IgAV) is a common small vessel vasculitis in children. Gastrointestinal perforation (GP) rarely presents as a complication of IgAV and is not well characterized. This study is aimed to investigate the clinical features, diagnosis, and risk factors of GP in children with IgAV. Methods We retrospectively reviewed the clinical data of children with IgAV who attended our hospital between January 2014 and June 2018. The clinical risk factors and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Guo et al's study did not discuss laboratory data as risk factors for GI bleeding or gastrointestinal perforation, focusing instead on the importance of history taking, past medical history, and findings from physical examinations (13). In contrast, our study analyzed both clinical and paraclinical data, representing a specific strength of our research.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Guo et al's study did not discuss laboratory data as risk factors for GI bleeding or gastrointestinal perforation, focusing instead on the importance of history taking, past medical history, and findings from physical examinations (13). In contrast, our study analyzed both clinical and paraclinical data, representing a specific strength of our research.…”
Section: Discussionmentioning
confidence: 96%
“…In 2021, Guo et al published research focusing on the clinical characteristics and risk factors of gastrointestinal perforation in children with small vessel vasculitis (13). Their retrospective study analyzed a cohort of 10,971 children with HSP from 2014 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al reviewed 10,791 children with IgAV and retrospectively analyzed the risk of gastrointestinal perforation, which occurred in 11 cases (0.1%). Prolonged abdominal pain (>7 days) and the administration of methylprednisolone (>2 mg/kg) were related to an increased risk of gastrointestinal perforation ( 9 ). A case-control study of 60 children with IgAV revealed 4 independent risk factors for intussusception in pediatric IgAV with GI involvement: age at onset, not receiving glucocorticoid therapy within 72 hours of the emergence of GI symptoms, positive stool blood test, and elevated D-dimer levels ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, an abdominal pain duration of more than seven days and a methylprednisolone dose of over 2 mg/kg increased gastrointestinal perforation in children with HSP. 20 The HSP in children with intermittent abdominal pain had a high risk of nephritis and severe GI bleeding. These patients should be followed up strictly with clinical and laboratory assessments, mainly during the first month of the disease course.…”
Section: Discussionmentioning
confidence: 99%